THE ROLE OF CREW ROSTERING IN SUSTAINABLE OPERATIONS: A CASE STUDY IN AIRLINES - Sarigol, Ilkan; Ozdemir, Rifat; AlAjmia, Amal; AlShammaria, Anwar; AlKafeefa, Mariam; Bukhsha, Mona; Al Ajmia, Reem (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
The airline industry has evolved significantly in recent years, and the emphasis on minimizing the cost and risk of operational disruptions has been shifted, in part, to satisfaction and fairness in the assignment of crew members. The crew rostering is the phase of flight schedules in which crew members are assigned to rosters based on their preferences and fairness in terms of balanced flight times between crew members. The satisfaction of the crew members depends on how much their preferences are met in the rosters. In this study, the crew rostering problem with cabin members’ preferences is formulated as a mixed-integer goal programming model with three objective functions: total satisfaction score, deviation from average satisfaction score, and deviation from average flight hours. The importance of these objectives is imprecise from the flight management system perspective, so this study proposes a fuzzy goal programming model to solve the crew rostering problem with the preferences. The paper is organized based on a case study gathered from an airline in Kuwait. The results showed that incorporating pilot preferences leads to better rosters in terms of pilot satisfaction. However, increasing the number of pilots in consideration or the flight evaluation percentage does not lead to better rosters. The case study also sheds light on the links between the crew roster and sustainable operations.